The construction of the definition of behavioural marketing in the perspective of the philosophy of science. An attempt at international confirmation - Jan Władysław Wiktor (Journal of Modern Science)
Objectives The aim of the article is to discuss the definition of behavioural marketing, an attempt to conceptualise and confirm it in the international dimension. Such a goal is an open scientific problem, arising from the lack of a precise definition of the category under study, or, in other words, the definition of behavioural marketing by a diverse set of elements of the definiens.